Peningkatan Literasi Digital UMKM melalui Pelatihan Pemanfaatan Internet dan Email pada MEK PCM Rungkut - Hafidz, Mohammad Al; Pratama, Yudha Herlambang Cahya; Ardianto, Herwin (Universitas Dinamika, 2026)
Micro, small, and medium enterprises (MSMEs) in the MEK PCM Rungkut area face challenges in digital literacy, particularly in searching for information online, accessing relevant websites, and using email for business communication. These limitations hinder their operational activities, reduce opportunities to utilize digital platforms, and restrict access to broader market opportunities. This community service program is designed to improve the basic digital skills of MSMEs through digital literacy training on the use of internet and email. The methods employed include observation and interviews to identify partner needs, training on information searching, website access, and email usage, as well as evaluation through pre- and post-tests. Data analysis was conducted using a descriptive approach and the Wilcoxon Signed Rank Test. The results showed that 18 out of 20 participants experienced an increase in their post-test scores, with all final scores reaching ≥ 70, indicating that the minimum competency standard had been achieved. The Wilcoxon test yielded a p-value of 0.012 (p < 0.05), indicating a significant improvement in participants' understanding before and after the training. In addition, participants demonstrated positive changes in independently seeking information and using email for business purposes. This study concludes that the program was effective in improving basic digital literacy among MSMEs. Further recommendations include continuous mentoring to support participants in developing more advanced digital skills, particularly in digital marketing and the utilization of other technology-based services.